Social mediators of relationships between childhood reading difficulties, behaviour problems, and secondary school noncompletion. (18th September 2018) - Smart, Diana; Youssef, George J.; Sanson, Ann; Prior, Margot; Toumbourou, John W.; Olsson, Craig A.
Abstract : Background: Childhood reading difficulties (RDs) and behaviour problems (BPs) are well‐established predictors of secondary school noncompletion. However, few studies have examined the risk of secondary school noncompletion for children with differing combinations of the two childhood problems. Even less is known about potential mediators of relationships between the two childhood problems and secondary school noncompletion. Aims: This study examined whether key indicators of social connectedness—adolescent school engagement, and family and peer attachment—mediated relationships between childhood RDs and BPs and secondary school noncompletion. Sample: Data were drawn from the Australian Temperament Project, a longitudinal study that has followed a large community sample across 16 waves from infancy to adulthood. Methods: Using standard reading and BP assessments, four childhood exposure groups were identified at 7–8 years: RDs‐only, BPs‐only, RDs + BPs, and Neither Problem. Results: Both groups with prior BPs had significantly poorer early‐adolescent school engagement, and family and peer attachment than the RDs‐only and Neither groups. School engagement mediated the relationship between childhood BPs and secondary school noncompletion but there was no evidence of similar mediation by family or peer attachment. Adolescent social connections did not mediate the effects of childhood RDs. Conclusions: The adverse long‐term consequences of childhood BPs on secondary school noncompletion may be alleviated by targeting adolescent school engagement. Intervention implications are discussed.